Umpasa dalam Ritual Saur Matua Budaya Batak Toba (kajian semiotika) - Lamria Romaito Sidabutar; Rosmawaty Harahap; Elly Prihasti Wuriyani (Medan Resource Center, 2022)
Toba Batak culture has a variety of unique and distinctive cultural riches. This can be seen from the cultural elements that are different from other cultures. One of the Toba Batak cultural traditions that is still preserved today, namely Umpasa. The richness of the Toba Batak culture still exists today. Umpasa is an oral tradition in the form of rhymes used by the Toba Batak cultural community to convey messages in the form of wishes, hopes, and other life values. This Toba Batak oral literature is used by local people on certain occasions. One of them is Umpasa in the Saur Matua ritual. In this context, Umpasa saur matua expresses the feelings experienced and expresses compassion for the events that occurred. In addition, the umpasa used also contains various values, such as religious values, namely the presence of God in life, family values, namely in conveying the umpasa there is a family relationship seen from the family line, and the value of deliberation, namely upholding mutual respect between relatives.